Removal of Acid Blue 158 from Solution by Sunflower Seed Hull - Siriwan Srisorrachatr; Paranee Sriromreun (ASEAN Journal of Chemical Engineering, 2013)
The removal of Acid Blue 158, acid dye for textile dyeing, from aqueous solution by sunflower seed hull was studied. The extent of adsorption capacity was studied as a function of heating temperature, sulphuric acid treatment, adsorbent size and pH of the solution. Sunflower seed hull was heated at 200, 300 and 400oC in oxygen deficient conditioned furnace. As the results, the sunflower seed hull heated at 200oC was the best absorbent for the dye removal with the maximum value of 30.84% at pH 4. Furthermore, removal ratio of Acid Blue 158 increased when the adsorbent was treated with 2M sulphuric acid. Particle sizes examined in this study were 250-355, 710-2000 and over 2000 micrometer. It was showed that the size of adsorbent affected on the removal capacity, i.e. the removal capacity increased along with the decrease of the size of absorbent. pH of the solution was studied between 1 and 6, and it was found that the optimum pH was pH 2. At the optimum condition, the modified adsorbent showed the removal ability of about 50%. The results obtained under the conditions of pH 4, 2M H2SO4 treatment of sunflower seed hull and the size of 500-710 micrometer at room temperature, the adsorption isotherm was fitted to Langmuir adsorption model, and the maximum adsorption capacity, qm, of 18.52 mg/g and Langmuir adsorption constant, Kl, of 5.25x10-3 L/mg were obtained.